Evaluation of an automated double-synthesis module: efficiency and reliability of subsequent radiosyntheses of FHBG and FLT - Niedermoser, Sabrina; Wängler, Björn (Nuclear medicine and biology, 2012)
We optimized the synthesis methods for 3′-deoxy-3′-[18F]fluorothymidine ([18F]FLT) and 9-(4-[18F]fluoro-3-[hydroxymethyl]butyl)guanine) ([18F]FHBG) and automated them on an Explora General Nucleophilic double-synthesis module. Furthermore, the synthesis efficiency and reliability and the formation of cross-contaminations of the products when preparing two consecutive batches were evaluated. Whereas the preinstalled FLT synthesis conditions required substantial modification in reaction and neutralization conditions to achieve radiochemical yields of up to 60% within 70±10 min including high-performance liquid chromatography purification, the synthesis of FHBG had to be implemented to the module to obtain competitive radiochemical yields of up to 40% in an overall synthesis time of 60±10 min. The radiochemical purities obtained were ≥99% and ≥96% for the synthesis of [18F]FLT and [18F]FHBG, respectively. No significant changes in yield or purity could be observed between both batch productions. We found that the yields and purities also did not change when performing FLT after FHBG syntheses and vice versa. Hence, we developed a synthesis setup that offers the opportunity to perform two subsequent syntheses of either [18F]FLT, [18F]FHBG or [18F]FLT after [18F]FHBG without decrease in radiochemical yields and purities. Also, no cross-contaminations were observed, which can be attributed to the use of separate product delivery tubes, purification columns and an automated intermediate cleaning program. These results open up the possibility of producing consecutively either two equal 18F-fluorinated tracers or two different ones in high yields on the same synthesis module.